An in-depth spectroscopic examination of molecular bands from 3D hydrodynamical model atmospheres: I. Formation of the G-band in metal-poor dwarf stars - Gallagher, Andrew J.; Caffau, Elisabetta; Ludwig, Hans-Günter (Arxiv, 2016)
Recent developments in the three-dimensional (3D) spectral synthesis code Linfor3D have meant that, for the first time, large spectral wavelength regions, such as molecular bands, can be synthesised with it in a short amount of time. A detailed spectral analysis of the synthetic G-band for several dwarf turn-off-type 3D atmospheres (5850 <= T_eff [K] <= 6550, 4.0 <= log g <= 4.5, -3.0 <= [Fe/H] <= -1.0) was conducted, under the assumption of local thermodynamic equilibrium. We also examine carbon and oxygen molecule formation at various metallicity regimes and discuss the impact it has on the G-band. Using a qualitative approach, we describe the different behaviours between the 3D atmospheres and the traditional one-dimensional (1D) atmospheres and how the different physics involved inevitably leads to abundance corrections, which differ over varying metallicities. Spectra computed in 1D were fit to every 3D spectrum to determine the 3D abundance correction. Early analysis revealed that the CH molecules that make up the G-band exhibited an oxygen abundance dependency; a higher oxygen abundance leads to weaker CH features. Nitrogen abundances showed zero impact to CH formation. The 3D corrections are also stronger at lower metallicity. Analysis of the 3D corrections to the G-band allows us to assign estimations of the 3D abundance correction to most dwarf stars presented in the literature. The 3D corrections suggest that A(C) in CEMP stars with high A(C) would remain unchanged, but would decrease in CEMP stars with lower A(C). It was found that the C/O ratio is an important parameter to the G-band in 3D. Additional testing confirmed that the C/O ratio is an equally important parameter for OH transitions under 3D. This presents a clear interrelation between the carbon and oxygen abundances in 3D atmospheres through their molecular species, which is not seen in 1D.